(3OaY GdeVGQ GdcdjI Yf GdCHOGf GdEfSGfjIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HYO GdMeO ddg hHYO ,aEf GdTjN GdLdjd CMeO GdSgdi NhGQRe hgh eef YQa HYdh Gdgeg hTQa GdCQheI s
(3BNQgG (B:s
(3hCeG efY GdESgGd Ch JOHjQ ef de jJSgd , agh ehLhO ai GdcJH , hdjcf gPG cGa ai ZQVfG s
(3fSNI KGdKIs
(3eWGHbI ai GdfU hGdGSe dfSNI ShgGL(B100s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B97 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs